2008
DOI: 10.1242/jcs.031195
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of flagellar oscillation–bending-induced switching of dynein activity in elastase-treated axonemes of sea urchin sperm

Abstract: Oscillatory movement of eukaryotic flagella is caused by dynein-driven microtubule sliding in the axoneme. The mechanical feedback from the bending itself is involved in the regulation of dynein activity, the main mechanism of which is thought to be switching of the activity of dynein between the two sides of the central pair microtubules. To test this, we developed an experimental system using elastase-treated axonemes of sperm flagella, which have a large Ca2+-induced principal bend (P-bend) at the base. On … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 39 publications
2
64
0
Order By: Relevance
“…4F), its deficiency could impair the initiation of pro-hook bend. A shortened doublet 7 would perturb any feedback system from distal to proximal flagellum (Hayashi and Shingyoji, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…4F), its deficiency could impair the initiation of pro-hook bend. A shortened doublet 7 would perturb any feedback system from distal to proximal flagellum (Hayashi and Shingyoji, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…By looking at individual doublet pairs sticking out from the frayed end of a Chlamydomonas flagellum, they showed that the pairs of doublets set up a limited beat of their own by sliding and bending to a critical bend angle and then separating near the base where the t-force is greatest. Recent important studies have demonstrated that imposed bending can initiate and reverse episodes of sliding in sea urchin sperm flagella when the doublets have been freed to slide by enzymatically cutting the nexin links with elastase (Morita and Shingyoji, 2004;Hayashi and Shingyoji, 2008); moreover, imposed bending can initiate beating at very low ATP concentrations (Ishikawa and Shingyoji, 2007). These results demonstrated that the curvature imposed on the partially digested structure controls the direction of dynein-driven sliding as the axoneme disintegrates.…”
Section: Bending-induced Slidingmentioning
confidence: 97%
“…It is equally possible that the action of the bending is mediated through a mechanism that senses the direction and degree of spoke tilting and relays an activating signal to the dyneins on one side, Recent reports (Morita and Shingyoji, 2004;Hayashi and Shingyoji, 2008) have shown that bending can initiate microtubule sliding and can determine which doublets are activated. The illustration shows a mechanism that might be responsible for the selection, but does not invoke CP-or spoke-dependent regulation.…”
Section: Bending-induced Slidingmentioning
confidence: 99%
“…There has been a report on using axonemal tubulin (95%)-derived microtubules for the in vitro motility assay of axonemal dynein, but it only shows higher velocity in short (<6 µm) conspecific microtubules than those polymerized from porcine brain tubulin (100%), and does not show any significant difference in longer microtubules (Alper et al, 2013; see the next section for the description of the lengths of the microtubules used in the present study). Micromanipulation was carried out according to our previously developed method (Morita and Shingyoji, 2004;Hayashi and Shingyoji, 2008) with some modifications. In our open-surface chamber, sliding velocity of the microtubules was 4.6±1.1 µm s −1 (mean±s.d.…”
Section: Microtubule Sliding Induced By Dyneins In the Open Surface Cmentioning
confidence: 99%
“…How are the dynein activities regulated and coordinated in flagella? Studies using intact sperm or demembranated flagellar axonemes have revealed that the sliding activities of dynein can be modulated by external strain or bending imposed to the axoneme when dynein is within the 9+2 structure of a flagellum (Gibbons et al, 1987;Shingyoji et al, 1991;Morita and Shingyoji, 2004;Hayashi and Shingyoji, 2008). This leads to an idea of the 'feedback regulation' of dynein in the axoneme, in which the inter-doublet sliding induced by dynein results in the bending of the axoneme, and the bending regulates the dynein activities in turn.…”
Section: Introductionmentioning
confidence: 99%